Tourism in Middle East and North Africa : A Strategy to Promote Recovery, Economic Diversification and Job Creation - Bell, Simon C.; Malinska, Jana; McConaghy, Peter; Al Rowais, Sara (World Bank, Washington, DC, 2014)
Often described as the cradle of civilization, the Middle East and North Africa (MENA) region boasts rich cultural assets, and is the historical origin of major religions including Christianity, Judaism, and Islam. This cultural heritage, coupled with the region s rich natural wonders, has made tourism a critical sector for economic and social development in the region. Tourism is a vital source of foreign exchange earnings, infrastructure investment, and cross-sectoral linkages. Even more importantly, the sector is a key source of job creation that can help MENA countries move from low value manufacturing into higher value-added service oriented activities. As many countries in the region transition to new governments, economic reforms can be undertaken to liberalize the sector, breaking down monopolistic market structures that prevent new entrants and stifle innovation. Similarly, there are new opportunities to develop a full-suite of tourism services (ecological, cultural, and religious tourism). Effective reform in the sector will require structural and regulatory changes that promote competition, strategic investment in infrastructure, targeted marketing, and a focus on training to address labor-skill mismatches, particularly for women and youth.